Fundamentals of agile project management : an overview - Goncalves, Marcus (American Society of Mechanical Engineers, 2010)
Introduction to agile methods for managing projects. Agile methods have been around for a while, but their prevalence has increased as the result of many successful projects in organizations that have applied them. While some of the agile methods discussed here spring from software development experiences, it is essential to understand that the underlying principles can be applied with appropriate modifications to any industry or organization.
Title from PDF title page (ASME eBooks Web site, viewed 12/04/2010).
Keywords: Project management.; Production management.; Flexible manufacturing systems.; System design.; elektronické knihy; electronic books